صناعة الهندسة المالية الإسلامية ودورها في تطوير سوق رأس المال الإسلامي - نصبه, مسعودة; السبتي, وسيلة (Recherches économiques et managériales; No 22 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2018)
إن الممارسات غير الأخلاقية التي تميز سوق رأس المال التقليدي من بيع صوري وشراء بغرض الاحتكار واستغلال ثقة العملاء وتلاعب في الأسعار إلى غير ذلك، يؤكد أهمية وضرورة إيجاد سوق رأس مال إسلامي ودعمه بالأدوات الاستثمارية الشرعية وتميزه بضوابط أخلاقية وخضوعه للرقابة الشرعية، دون نكران الحاجة إلى الابتكار والإبداع من أجل أن يقوم بالدور الاقتصادي المؤمل منها، لتحقيق مصالح المسلمين الاقتصادية المتوافقة مع شريعتهم . تعتبر الهندسة المالية الإسلامية الأداة الأنسب التي يمكنها تقديم مساعدة فعالة لتحقيق الأهداف الإستراتجية التي تخطط لها المؤسسات المالية الإسلامية، وتسعى إلى قيام هذه المؤسسات برسم سياسات مالية قوية وتطوير وابتكار منتجات وأدوات مالية جديدة وآليات واستراتجيات مالية مرنة من شأنها تطوير سوق رأس المال الإسلامي، أي محاولة جعل هذه التغيرات مفيدة بدلا من اعتبارها مصدر خطر عليها . الكلمات المفتاحية : الهندسة المالية الإسلامية، سوق رأس المال الإسلامي، الرقابة الشرعية Abstract : The unethical practices that characterize the traditional capital market from selling images, buying for monopoly purposes, exploiting customer confidence, manipulating prices, etc., emphasizes the importance and necessity of creating an Islamic capital market and supporting it with legitimate investment tools and characterized by ethical controls and obedience to legal supervision, without denying the need for innovation. And creativity in order to play the economic role of the hope, to achieve the interests of Muslims economic compatible with their legislation. Islamic Finance is the most appropriate tool that can provide effective assistance to achieve the strategic objectives of Islamic financial institutions. It seeks to create strong financial policies, develop and innovate new financial instruments and mechanisms, and flexible financial mechanisms and strategies that will develop the Islamic capital market. Making these changes useful rather than being considered a source of danger . key words  Islamic Financial Engineering Islamic Capital Market Sharia Control